1970
DOI: 10.4153/cmb-1970-093-0
|View full text |Cite
|
Sign up to set email alerts
|

On the Minimal Graph with a Given Number of Spanning Trees

Abstract: Let G be a finite connected graph without loops or multiple edges. A maximal tree subgraph T of G is called a spanning tree of G. Denote by k(G) the number of all trees spanning the graph G. A. Rosa formulated the following problem (private communication): Let x(≠2) be a given positive integer and denote by α(x) the smallest positive integer y having the following property: There exists a graph G on y vertices with x spanning trees. Investigate the behavior of the function α(x).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…these are the only numbers n such that α(n) = n. He also defined the function β(n) as the least number of edges l for which there exists a graph with l edges and with precisely n spanning trees. He showed that α(n) < β(n) n + 1 2 , except for the fixed points of α in which case it holds that α(n) = β(n) = n. Moreover, as is observed in [8], from the construction used by Sedláček [7] we have…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…these are the only numbers n such that α(n) = n. He also defined the function β(n) as the least number of edges l for which there exists a graph with l edges and with precisely n spanning trees. He showed that α(n) < β(n) n + 1 2 , except for the fixed points of α in which case it holds that α(n) = β(n) = n. Moreover, as is observed in [8], from the construction used by Sedláček [7] we have…”
Section: Introductionmentioning
confidence: 74%
“…We use this number theoretical result to improve the answer related to the question Sedláček [7] posed in 1970: Given a number n 3, what is the least number k such that there exists a graph on k vertices having precisely n spanning trees? Sedláček denoted this function by α(n).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously a(x) ^ fi(x) ^ x, for any x ^ 3. The function a has been studied by J. SEDLACEK [3], who also gave an impulse to the rise of the present paper.…”
mentioning
confidence: 92%
“…The very simple generalization of one of the procedures used in [3] for the estimate of the function a leads to the following estimate of the function p which is given by graphs with at least one separating vertex: if x x and x 2 are integers and…”
mentioning
confidence: 99%
See 1 more Smart Citation